UJI KELAYAKAN PANTAI TEBING KARANG KERAKAS SEBAGAI LOKASI RUKYATUL HILAL - Shintiya, Shintiya Desvi Triyan Putri; Rizal, Ahmad Ashril (UIN ALAUDDIN MAKASSAR, 2024)
The main issue in rukyatul hilal is the difference in perspective between the hisab and rukyat methods in determining the beginning of the lunar month, which often leads to confusion and debate among Muslims. Additionally, the success of hilal observation is influenced by various factors such as weather conditions, air quality, and site selection, making it important to assess the suitability of observation locations like Pantai Tebing Karang Kerakas in Lombok. This study aims to evaluate the feasibility of Pantai Tebing Karang Kerakas as a rukyatul hilal location. It employs a field research approach with a mixed-method research design, combining qualitative and quantitative research to assess the site's suitability. The researcher conducted direct observations of the geographical, astronomical, and climatological conditions using telescopes and cameras, and analyzed the data descriptively and comparatively to provide a comprehensive overview. The results indicate that geographically and astronomically, Pantai Tebing Karang Kerakas does not meet the clear view criteria for the azimuth range of 240-300 degrees. Specifically, Mount Agung obstructs the view at azimuth 248, and at azimuth 270, the sky is often covered with thick clouds, hindering hilal observation. Meteorologically, as discussed in the previous chapter, the weather at Pantai Tebing is less favorable during certain months. High rainfall in the region leads to thick cloud formation, frequently obstructing or failing hilal observations.